Research on Comparative Analysis Toxic Effect of Formalin on MBBS Students of Several Medical College in Bangladesh - Uddin, Mohammad Nasir; Miah, Ismail; Akter, Nasrin (European Scientific Journal, ESJ, 2019)
Formaldehyde is a common indoor pollutant with irritant properties. The evaporation of formaldehyde from cadavers in gross anatomy laboratories can produce high exposure among students and instructors. This study was conducted to assess acute toxic effects of formalin during dissection classes on medical students at the anatomy department in Armed forces medical college, Dhaka (AFMC), Army medical college, Cumilla (AMCC), and Eastern medical college, Cumilla (EMCC) in Bangladesh. A cross sectional approach was adopted to investigate medical students of AFMC (n=125), AMCC (n=50), & EMCC (n=75).Every medical students filled self administered predesigned questionnaire and submitted research authority. The most frequently reported symptoms by medical students of AFMC, AMCC & EMCC were unfavorable scent (84.8%, 86%, 76%), Tearing of eyes (84.8%, 90%, 72%), Running nose with prickling sensibility (61.6%, 82%, 65.33%), Neuralgia/migraine (52%, 86%, 62.67%), Inflammation of eyes (63.2%, 84%, 66.67%), Inconvenience inhale & exhale (72.8%, 86%, 66.67%) , Qualm (80%, 84%, 60%,) Extreme tears/ lacrimation (87.2%, 86% , 49.33%), Sore aphonia/throat(49.6%, 64%, 66.67%), Scabies (53.6%, 78%, 62.67%), Giddiness (63.2%, 72%, 64%), and Blister(52%, 70%, and 65.33%) respectively. Moreover in the current research 69.67%, students of AFMC reported wearing laboratory aprons 56.8%, reported wearing hand gloves and 5.6%, reported wearing eye goggles, where as 92%, of AMCC students reported wearing laboratory aprons/ coat 74%, student wearing hand gloves and 14%,students wearing eye goggles. On the other hand 73.33% of EMCC student reported wearing laboratory aprons 62.67%, students wearing hand gloves as well as only 21.33% students reported wearing eye goggles to protect formalin toxicity. So this research highlighted the irritation action of formalin on medical students during dissection classes in Anatomy department. The harmful effects of formalin can be reduced by some preventive measures like good exhaust ventilation by reducing the concentration of formalin in embalming fluid or using alternative for formalin in the form of phenoxyethanol.